2008
DOI: 10.1016/j.phytochem.2008.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and biotechnological application of an acid α-galactosidase from Tachigali multijuga Benth. seeds

Abstract: Tachigali multijuga Benth. seeds were found to contain protein (364 mg g(-1)dwt), lipids (24 mg g(-1)dwt), ash (35 mg g(-1)dwt), and carbohydrates (577 mg g(-1)dwt). Sucrose, raffinose, and stachyose concentrations were 8.3, 3.0, and 11.6 mg g(-1)dwt, respectively. alpha-Galactosidase activity increased during seed germination and reached a maximum level at 108 h after seed imbibition. The alpha-galactosidase purified from germinating seeds had an M(r) of 38,000 and maximal activity at pH 5.0-5.5 and 50 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…One group was specific for smaller α-galactosides, such as alkyl-and aryl-galactosides, melibiose and oligosaccharides and other group acted on polymeric galactomannan and also hydrolyzed smaller substrates to various extents. A. terreus α-galactosidases could be grouped in the second category, such as α-galactosidases from D. hansenii [27], AGL I and AGL III from Penicillium simplicissimum [40], and α-galactosidase from Tachigali multijuga seeds [41]. The ability to hydrolyze guar gum and locust bean gum also showed that A. terreus α-galactosidases may be useful industrially for improving the gelling properties of polysaccharides [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One group was specific for smaller α-galactosides, such as alkyl-and aryl-galactosides, melibiose and oligosaccharides and other group acted on polymeric galactomannan and also hydrolyzed smaller substrates to various extents. A. terreus α-galactosidases could be grouped in the second category, such as α-galactosidases from D. hansenii [27], AGL I and AGL III from Penicillium simplicissimum [40], and α-galactosidase from Tachigali multijuga seeds [41]. The ability to hydrolyze guar gum and locust bean gum also showed that A. terreus α-galactosidases may be useful industrially for improving the gelling properties of polysaccharides [42].…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of enzyme activity by metal cations, such as Hg 2+ , Ag + , and Cu 2+ usually suggests reaction with thiol groups and/or carboxyl, amino and imidazolium groups of histidine in the active site [47]. The inhibition of α-galactosidases by Hg 2+ , Ag + , and Cu 2 + is a classical result, which was reported for several microbial [2,7,27,35,44,48] and plant [19,41,49] α-galactosidases. The activity of A. terreus α-galactosidases was not affected by EDTA, indicating that the enzymes were not a metalloenzymes.…”
Section: Resultsmentioning
confidence: 99%
“…However, it might still have several applications in other fields. For example, in the food industry, there have already been several reports on the use of GLA from plants, 49 bacteria, 50 yeast, 51 and fungal sources 52 for the removal of raffinosefamily sugars, the major factors responsible for flatulence following ingestion of soybean and legumes. GLA is also known to remove a large proportion of galactose moieties from guar (Cyamopsis tetragonoloba) gum, improving its gelling properties, and GLA-modified galactomannan has been used to improve the gelling properties of some polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the activity data of the α-galactosidase enzyme in the cotyledons with the increasing levels of galactose (Figure 2), which is one of the products resulting from the action of this enzyme, it can be seen that although the activity of the enzyme stays practically constant for all levels of water content in both lots, the increase in the concentration of galactose confirms the assumption that this accumulation does not come from the continual increase of product but from accumulation due to less use or leakage of the apoplast. The activity of α-galactosidase increased during the germination of Tachigali multijuga seeds, associated with the reduction in raffinose and stachyose levels, so that seed hydration during imbibition possibly induced α-galactosidase activity, resulting in a breakage of the oligosaccharids, which are indirectly involved in energy production (Fialho et al, 2008). The activity of polygalacturonase detected during hydration of the Dalbergia nigra seeds in the two lots evaluated indicates that this enzyme is pre-existing in both lots (Figure 4).…”
Section: Resultsmentioning
confidence: 97%
“…The hydrolytic enzyme α-galactosidase acts in the mobilization of polysaccharides and cell wall components and in oligosaccharides of the raffinosic series, and its degradation products are used to generate energy and produce raw materials for germination, among other things (Buckeridge et al, 2004). The activity of the α-galactosidase enzyme increased during the germination of Tachigali multijuga seeds, being related to the capacity to hydrolyze oligosaccharides, such as raffinose, stachyose and galactomannan polymers, indicating a special role during germination (Fialho et al, 2008). According to Polowick et al (2009), after super expression of the α-galactosidase gene in Pisum sativum seeds, the lines showed significant reductions in oligosaccharides, specifically raffinose and stachyose, and germination rates were 96%.…”
Section: Introductionmentioning
confidence: 99%